The Diuretic Effect of Sairei-to Is Mediated by Nitric Oxide Production in Pentobarbital-Anesthetized Rats - Naoki Fujitsuka; Kazuhiro Goto; Shuichi Takeda; Masaki Aburada (Elsevier, 2004)
Sairei-to (TJ-114), a Japanese traditional medicine, has been used clinically for the treatment of various edematous disorders. The inhibitory effect on edema may be dependent on the diuretic response to TJ-114. This study was conducted to clarify the mechanism of diuresis. Pentobarbital-anesthetized rats were infused with a saline solution intravenously (0.4 mL/30 min). Urine was collected through a bladder cannula for 30 min. Intraduodenal administration of TJ-114 (0.5 - 1.5 g/kg) resulted in a dose-dependent increase of urine volume with insignificant urinary sodium excretion and significant urea excretion, but no effect on mean arterial blood pressure. Furthermore, TJ-114 significantly increased urinary levels of NO2 +NO3. In addition, intraperitoneal pre-treatment with 6 mg/kg of NG-nitro-L-arginine methyl ester inhibited the increase in urine volume, urinary urea excretion, and urinary levels of NO2 +NO3 in the rats treated with TJ-114. These results suggest that TJ-114 induces a diuretic response via production of NO. Keywords:: Sairei-to, nitric oxide, diuresis, edema